EXPLORING THE ROLE OF EXAMPLE PROBLEM-BASED LEARNING IN MANAGING STUDENTS' COGNITIVE LOAD DURING COMPLEX MATHEMATICAL PROBLEM SOLVING - Nadia Rizqi; Cecep Anwar Hadi Firdos Santosa; Jaenudin Jaenudin (Universitas Sembilanbelas November Kolaka, 2026)
This study aims to validate the effect of EPBL in reducing students' cognitive load in solving complex mathematical problems. It also examines the impact of EPBL implementation on students learning process. This study uses a mixed-method approach with a concurrent triangulation design. The subjects of this study were one 8th-grade class at SMP Negeri 14 Kota Serang, consisting of 36 students. Quantitative data were analyzed using paired t-test statistics, while qualitative data obtained through semi-structured interviews were analyzed using thematic analysis. The results showed that the implementation of EPBL significantly improved students' mathematical problem-solving abilities. The average score increased from 47.50 in the pretest to 76.39 in the posttest, with an effect size of 1.011, which is considered large. The results also showed a significant decrease in students' cognitive load, with the average score decreasing from 50.25 to 17.00 and an effect size of 2.269, which is considered very large. Qualitative findings support these results through two main themes: ease of understanding the material and learning comfort. Students stated that the use of worked examples helped them understand concepts and problem-solving procedures more effectively, while the structured learning process created a more comfortable learning atmosphere. The findings of this study indicate that EPBL contributes to improving mathematical problem-solving skills while helping reduce students' cognitive load in solving complex mathematical problems. This study provides empirical evidence regarding the effectiveness of integrating worked examples and problem-solving activities as a mathematics learning strategy that supports students' cognitive load management.